The role of soluble epoxide hydrolase in preeclampsia. (October 2017) - Santos, Julia M.; Park, Jung-A.; Joiakim, Aby; Putt, David A.; Taylor, Robert N.; Kim, Hyesook
Abstract: Preeclampsia is a serious complication of pregnancy characterized by the development of vasospasm, hypertension and often associated with proteinuria after the 20th week of gestation. Because termination of pregnancy results in the most efficacious resolution of preeclampsia, it is a leading cause of premature delivery worldwide. In pregnancy, 14, 15-epoxyeicosatrienoic acids (EETs) have been shown to facilitate uterine blood flow during preeclampsia, in which the classic vasodilator agents such as nitric oxide and prostacyclin are reduced. EETs are converted to dihydroxyeicosatrienoic acids (DHETs) by the activity of soluble epoxide hydrolase (sEH). We tested the hypothesis that sEH activity is increased in preeclampsia by measuring urinary 14, 15-DHET in healthy and preeclamptic pregnant women. Urine samples were collected and incubated with or without β-glucuronidase to enable the measurement of both the glucuronidated and free forms of 14, 15-DHET, which were quantified using a 14, 15-DHET ELISA. Levels of total (free + glucuronidated) 14, 15-DHET, which is a measurement of EET-dependent sEH activity, were higher in urine samples obtained from preeclamptic women compared to healthy pregnant women. Considering the fact that free + glucuronidated 14, 15-DHET levels are increased in urine of preeclamptic women, we hypothesize that sEH expression or activity is augmented in these patients, reducing EET and increasing blood pressure. Moreover we suggest that novel anti-hypertensive agents that target sEH might be developed as therapeutics to control high blood pressure in women with preeclampsia.